Customary law : in the peasant community of Uripa (Raíces: Revista de Ciencias Sociales y Políticas, 2023)
Anthropology as a social science points to global diversity with geographical and historical extension in every sense, making visible in full the social norms of the customary law of each society. The objective was to describe and analyze the legal custom in Uripa, of the lands community, social organization and sanctions in the community that energizes traditional patterns as well as ancestral behaviors in life daily, generating new forms of control in the awareness of values social, moral and legal. With this it is evident, the social interrelation in collective memory, the set of norms and behavior that regulates the community. Finally, the relevance of the result is the manifestations of practices that develop over time, the complexity of tenure, the administration, moral commitment and social security.
Keywords: customary law; community; organization; territory and conduct